2016
DOI: 10.1161/circulationaha.116.023425
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Vessel Calibers in Predicting Long-Term Cardiovascular Outcomes

Abstract: Background Narrower retinal arterioles and wider retinal venules have been associated with negative cardiovascular outcomes. We investigated whether retinal vessel calibers are associated with cardiovascular outcomes in long-term follow-up and provide incremental value over the 2013 American College of Cardiology/American Heart Association pooled cohort equations (PCE) in predicting Atherosclerotic Cardiovascular Disease Events (ASCVE). Methods 10,470 men and women without prior ASCVE or heart failure (HF) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
185
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(195 citation statements)
references
References 46 publications
5
185
3
2
Order By: Relevance
“…The smaller and larger diameters are approximately normally distributed which allows for calculation of the equivalents according to Parr and Hubbard [58][59][60]. The ratio is a cardiovascular risk factor and predictor of long-term outcome [61].…”
Section: How Can We Measure Endothelial Function?mentioning
confidence: 99%
See 1 more Smart Citation
“…The smaller and larger diameters are approximately normally distributed which allows for calculation of the equivalents according to Parr and Hubbard [58][59][60]. The ratio is a cardiovascular risk factor and predictor of long-term outcome [61].…”
Section: How Can We Measure Endothelial Function?mentioning
confidence: 99%
“…Over 16 years of follow-up in 10,470 initially healthy individuals, it was shown that narrower retinal arterioles and wider venules confer a significant risk for ischemic stroke and all-cause mortality [61].…”
Section: Endothelial Dysfunction-a Hallmark Of Cardiovascular Diseasementioning
confidence: 99%
“…Technological advances now allow non‐invasive assessment of the microcirculation in large studies, most commonly by quantification of the retinal microvasculature . Adverse phenotypes of the retinal microcirculation (narrower retinal arteriolar and wider venular caliber) have also been associated with adverse CVD outcomes . For instance, the large Atherosclerosis Risk in Communities Study showed that, over a 16 years follow‐up period, generally healthy subjects with narrower arteriolar caliber and wider venular caliber had a higher risk of ischemic stroke in both sexes (hazard ratio 1.10, 95% CI 1.00 to 1.20 and 1.14, 95%CI 1.03 to 1.26, respectively) .…”
Section: Introductionmentioning
confidence: 99%
“…A number of retinal [1,2,3], cardiovascular [4] and systemic diseases [5] can be identified by studying the retinal vasculature and the morphological changes. Although retinal vascular alterations are subtle, early recognition of the signs can be paramount for helping prevent ophthalmologic complications and vision loss.…”
Section: Introductionmentioning
confidence: 99%